THE CONSTRUCTION OF A VISION OF RETURN IN THE SPANISH PUBLIC OPINION DURING THE YEARS OF THE GREAT IMMIGRATION WAVE (1880-1930) (Estudios de Historia de España, 2022)
Although the prospect of return is intrinsically present in most migration projects, this issue was relatively absent from public debates in Spain during the years of the so-called mass emigration (1880-1930). This article has three objectives. Firstly, it aims to understand why this issue played an almost marginal role in the debates of the time. Secondly, it will reconstruct the image of the "returnee" and analyse the conception that the press of the time had of the phenomenon of return and the way in which the state should (or should not) intervene in it. The third and final part will seek to determine the impact that these opinions and perceptions emanating from the public sphere had on the migration policy of those years.
Keywords: Migrations; Return; Public opinion; Political debates; Contemporary Spain